PP.16.39: ASSESSING ANTIHYPERTENSIVE ADHERENCE WITH THERAPEUTIC DRUG MONITORING. (June 2015) - Jones, E.; Decloedt, E.; Blockman, M.; Sturrock, E.; Lesosky, M.; Wiesner, L.; Castel, S.; Schwager, S.; Rayner, B.
Abstract : Objective: The proportion of South African hypertensive patients with controlled blood pressure (BP) is low. Non-adherence may play an important role but monitoring adherence remains difficult. Two commonly used antihypertensives are amlodipine and enalapril. This study aims to determine if monitoring amlodipine levels and inhibition of angiotensin converting enzyme (ACE) are feasible means to determine patient adherence. Design and method: Patients attending a referral clinic for resistant hypertension that were prescribed enalapril and amlodipine (±other antihypertensives) were enrolled. After informed consent patients underwent BP monitoring; a questionnaire on adherence and blood samples for amlodipine levels and ACE activity. Assessments were repeated. Amlodipine was assayed using liquid chromatography-mass spectrometry. The degree of ACE inhibition was determined by the z-phenylalanine-histidine-leucine and hippuryl-histidine-leucine ratio. Results: One hundred patients (age ± 50.5y and 46% male) were enrolled, with 65 follow-up assessments. There was no difference between the mean BP from visit 1 to 2. Most patients (90%) self medicated, and 24% used pillboxes. ACE Results Control data suggest a ratio <1.4 to be consistent with no ACE inhibition. Ten patients (17%) were found to be non-adherent at both visits and 12 (20%) at either visit 1 or 2; 38 (63%) were adherent at both visits. Five patients had missing data. There were significant differences in BP between adherent and non-adherent patients: 141 ± 22/84 ± 15 mmHg vs.168 ± 30/105 ± 18 mmHg for visit 1, (p < 0.0001); and 146 ± 23/86 ± 17 mmHg vs.172 ± 34/99 ± 22 mmHg for visit 2 (p = 0.002 for SBP and p = 0.19 for DBP). Amlodipine results An undetectable level of amlodipine was found at both visits in 10 (15.4%) patients and in 4 (6.2%) patients at either visit. Fifty-one (78.5%) patients were adherent at both visits. The BP of patients adherent to amlodipine at visit 1 was 141 ± 22/85 ± 14 mmHg vs. 176 ± 27/108 ± 19 mmHg in the non-adherent group, p < 0.0001. At visit 2 the adherent group had a BP of 148 ± 29/86 ± 17 mmHg vs. 173 ± 21/102 ± 22 mmHg, p = 0.008 and p = 0.005 for SBP and DBP. At both visits 67% of those non-adherent to amlodipine were non-adherent to enalapril. Conclusions: Monitoring antihypertensive adherence through therapeutic drug monitoring is a feasible option at the clinic. Non-adherence strongly predicts the presence of uncontrolled BP.